Transient ischemic dilation ratio in regadenoson, single isotope gated single-photon emission computed tomography myocardial perfusion imaging - Manolo Rubio; Andre Dias; Nikoloz Koshkelashvili; Jose Codolosa; Mauricio Jalife-Bucay; Mary Rodriguez-Ziccardi; Aman Amanullah (World Journal of Nuclear Medicine)
Single isotope 99mTc single-photon emission computed tomography-myocardial perfusion imaging (SPECT-MPI) is the most commonly used protocol for nuclear stress testing. Transient ischemic dilation of the left ventricle (TID) has been considered a specific marker of severe coronary artery disease (CAD). Recent publications have questioned the clinical utility of TID, specifically with regadenoson as a stressor and 4DM-SPECT software for TID analysis. These findings have not been demonstrated using other imaging packages. The goal of our study was to establish the TID threshold in the identification of Multi-vessel CAD using Quantitative Perfusion SPECT (QPS) software. Included in this study are 190 patients that had undergone regadenoson-stress, same day, single-isotope 99mTc MPI and had a coronary angiography within a designated 3-month period. QPS (Cedars-Sinai, LA, CA) automated image analysis software was used to calculate TID ratios which were compared across different CAD categories. Coronary angiograms were reviewed to identify both obstructive and nonobstructive CAD. The mean TID for patients with nonobstructive CAD (n = 91) was 1.02 ± 0.11, and the threshold for TID was 1.24. A receiver operating characteristic curve showed that TID had a poor discriminatory capacity to identify MVD (area under the curve 0.58) with a sensitivity of 3% and a specificity of 97%. In our study with regadenoson MPI in a predominantly African-American population, TID was found to be a poor predictor of MVD using QPS software. The reason is unclear but possibly related to the significant decline in the prevalence of severe CAD in the area where our study took place.